Extract Clove Leaves Were Used to Test the Effectiveness of Hand Washing Soap. Aedes Aegypti Mosquito Larvae Syzygium Aromaticum L Exterminator - Budiman Budiman; Nur Rismawati (International Journal of Health, Economics, and Social Sciences (IJHESS), 2022)
The best method for getting rid of mosquito larvae is to employ biological pesticides derived from plants, such as Syzygium aromaticum L.'s clove leaf extract. Aedes aegypti larvae can be killed by a clove leaf extract containing eugenol, saponins, flavonoids, and tannins. Insect repellent hand soap prepared from Syzygium aromaticum L clove leaf extract is being tested to see how well it works against Aedes aegypti mosquito larvae. This study uses an experimental design with a post-test and a control group, including three treatment and three control groups. A sample of 20 larvae was taken from each group and the control three times. So that there were 280 Aedes aegypti larvae in the sample, 60, 80, and 100 mL of hand soap prepared from Syzygium aromaticum L. clove leaf extract were used, respectively. Within 24 hours, observations were taken, and the number of larvae perished each hour was recorded. The outcomes demonstrated that the amount of Aedes aegypti larvae mortality in the treatment of 60 mL, 80 mL, and 100 mL was extremely effective, being able to kill 100 percent with three repetitions in one hour, non-treatment (negative control) 0 percent larvae mortality in time of 24 hours, and the control treatment of hand washing soap without clove leaf extract was less effective, it could only kill 50 percent within 24 am, while the control treatment with clove was more effective. The mortality of mosquito larvae is significantly influenced by the concentration of hand soap made from clove leaf extract Syzygium aromaticum L, which occurs extremely quickly. To promote public awareness and comprehension of natural larvae exterminators, there is a need to educate people about the risks of DHF and how to prevent it with natural components. The findings of this study are anticipated to be used in the future to improve health conditions.